Hemoadsorption in Multiorgan Failure Due to Viscerocutaneous Loxoscelism - Raúl Valenzuela Córdova; David Rivera Estrella; José F. Bernardo; Darío Jiménez; Celia Rodríguez Tudero; Raúl Elías; José C. De La Flor (Medicina)
Background: The bite of the Loxosceles spider is a public health problem around the world, mainly in Latin America. The viscerocutaneous presentation is related to the inoculation of toxins (phospholipase-D) that generates a systemic inflammatory reaction with a subsequent increase in cytokines and chemokines. Hemoadsorption is proposed as a therapy that allows for the removal of the toxin and modulation of the inflammatory response in this disease. Case Report: We present the case of a 31-year-old woman who was admitted to the hospital due to decreased urinary flow and jaundice 48 h after a spider bite. Despite treatment with intravenous (IV) monovalent antiloxoscelism serum, antibiotic therapy, and corticosteroids, the patient’s evolution was poor, and she was admitted to the critical care unit for severe multi-organ involvement, including hepatic and kidney damage and coagulation disorders, eventually requiring hemodialysis support and hemoadsorption therapy. After the therapy was administered, rapid improvement was evident with the suspension of vasopressor support and a decrease in inflammatory markers. Conclusions: This case presents hemoadsorption as a therapeutic option, based on its capacity to reduce the intensity of hyperinflammation and to regulate the immunological response.